PENGEMBANGAN E-BOOK BEREKSTENSI epub PADA PEMBELAJARAN IPA SMP - Haning Hasbiyati; Laila Khusnah (JURNAL BIOSHELL, 2016)
Specific targets are achieved from this research is to develop e-book in the smartphone as a medium of learning that is innovative as an attempt to renew following the progress of science and technology. The purpose long-term research is expected to reduce the burden of teachers in presenting the information in the study because it is represented by the e-book, can streamline and minimize the learning time because they do not have to carry a lot of books in the physical form of severe, and can help facilitate student learning for multimedia features can become a tutor. Analysis of the data in this research is the analysis of qualitative data obtained from the comments and suggestions of experts, while the quantitative data obtained from the results of the validation subject matter experts, and media specialists.Based on the validation results obtained materials experts concluded the average rate of 3.35 with product feasibility and based on the results obtained conclusions media expert validation average product eligibility rate of 3.67.Keywords: E-Book, epub, science